If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-4 * 2) + (-4 * 3b) + 5b = 13 Multiply -4 * 2 (-8) + (-4 * 3b) + 5b = 13 -8 + (-4 * 3b) + 5b = 13 Multiply -4 * 3 -8 + (-12b) + 5b = 13 Combine like terms: (-12b) + 5b = -7b -8 + -7b = 13 Solving -8 + -7b = 13 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -7b = 13 + 8 Combine like terms: -8 + 8 = 0 0 + -7b = 13 + 8 -7b = 13 + 8 Combine like terms: 13 + 8 = 21 -7b = 21 Divide each side by '-7'. b = -3 Simplifying b = -3
| x=1/2(3x-11) | | C+7+3c=5c+11 | | 0.3(x)=294 | | 9x+4x=22-6 | | 9m+63=27 | | 10+3y-2=4y+y+8 | | h=-16x^2+24 | | ×-1/2=5/4 | | 2x(25x^2-50x+25)-10x^2*(5-5x)=0 | | (-96)/(-16) | | exp(-10x)=0 | | 9=2x+10 | | e^9x=6.9 | | 34-u=197 | | 5f+11=f-6 | | (3x+25)=2 | | 9m+67=27 | | (-12)/(-2) | | 0.3/x=294 | | 18x+36=486 | | 13-(x-6)=9x-3 | | -0.4=-12x | | D=256/4 | | 2.5(2m+2)-3=m-12 | | 5r(4r+3)= | | -0.4=-12 | | X^3+2x^2+9x=0 | | 9x+4x=22-6x | | D=4*16 | | sinA=0.27 | | (2a+b+3c)2+(3a+2b-c)2= | | -7a(4a-4)= |